￼THE IMPROVEMENT OF SPEAKING ABILITY OF CHILDREN AGED 3-4 YEARS THROUGH MORNING MEETING ACTIVITIES - Fitri Ramadhini (Universitas Muhammadiyah Ponorogo, 2019)
This research aimed to explain the process and the result of using the “morning meeting” activities to improve the speaking ability of children aged 3-4 years in Kelompok Bermain 1 Sakinah Playgroup Al-Azhar Complex, East Jakarta in 2017. The research method used was a model of Kemmis Taggart spiral action research consisting of : (a) planning, (b) action and observation, and (c) reflection. The instruments used in this research were observation, interview, and documentation. The data scores of speech were analyzed using quantitative and qualitative approaches. The results showed that children's speaking skills have improved. If the pretest of children speaking ability significantly was 63.50%, in the first cycle, it became 71.45%. Scores in the second cycle increased by about 12.19% and scored 83.64%. The conclusion of this study is (1) the process of using the morning meeting activity could improve the speaking ability of children in Sakinah Playgroup Al-Azhar Complex in East Jakarta in 2017, (2) children's speaking ability in Sakinah Playgroup Complex Al-Azhar, East Jakarta in 2017 indicated an increase from pre-cycle to first cycle, and second cycle.